2013
DOI: 10.1309/ajcpimpe6zft8ame
|View full text |Cite
|
Sign up to set email alerts
|

Growth Pattern, an Important Pathologic Prognostic Parameter for Clear Cell Renal Cell Carcinoma

Abstract: Growth pattern can be considered a new prognostic parameter for ccRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Recently, we reported that the infiltrating pattern was related to poor clinical outcomes in patients with CCRCC. 13,14 In the present study, we further demonstrated that this new pathologic parameter is prognostic for patients treated with sorafenib. We observed an 8.7-month median duration of PFS in patients with an expansive pattern, which was considerably longer than the 1.7-month median PFS in patients with an infiltrating pattern.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Recently, we reported that the infiltrating pattern was related to poor clinical outcomes in patients with CCRCC. 13,14 In the present study, we further demonstrated that this new pathologic parameter is prognostic for patients treated with sorafenib. We observed an 8.7-month median duration of PFS in patients with an expansive pattern, which was considerably longer than the 1.7-month median PFS in patients with an infiltrating pattern.…”
Section: Discussionsupporting
confidence: 74%
“…13,14 However, no studies have investigated whether growth pattern could be used to predict the outcomes of patients with CCRCC who are receiving TKIs. Accordingly, we have retrospectively investigated the set of pathologic parameters that may be predictive of response rates and PFS in cases of metastatic CCRCC that are treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that an ill-defined tumor margin and tumor calcification each were associated with the BAP1 mutation. An ill-defined margin has been associated with locally infiltrative and overall aggressive ccRCC [5, 33, 34]. The BAP1 mutation, found in 15% of ccRCC, is known to be associated with high-grade tumors (Fuhrman grade 3 or 4) and poor survival [5, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In the final analysis, the success of TE in most of the recent series likely reflects the inherent tumor biology of cT1 RCC, which typically demonstrates expansive growth pattern rather than infiltration. 12 In summary, TE is a contemporary approach to sporadic RCC in the era of maximal nephron preservation. TE allows for equivalent oncologic control, enhanced surgical precision and the potential for fewer intraoperative complications, and may obviate the need for warm ischemia and complex renorrhaphy.…”
Section: Tumor Enucleation: Promentioning
confidence: 99%